2022
DOI: 10.24918/cs.2022.44
|View full text |Cite
|
Sign up to set email alerts
|

Online Information Literacy: Applying the CRAAP Test to Vaccine (Mis)information

Abstract: When you search for information, you're going to find lots of it . . . but is it good information? You will have to determine that for yourself, and the CRAAP Test can help. The CRAAP Test is a list of questions to help you evaluate the information you find. Different criteria will be more or less important depending on your situation or need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They argued that clear health communication is necessary when convincing someone to receive a vaccine. Holzhausen et al (2022) taught students how to apply the CRAAP test when evaluating information. They found that after this lesson, students were able to identify examples that contained vaccine misinformation.…”
Section: Information Literacy During the Covid-19 Pandemicmentioning
confidence: 99%
“…They argued that clear health communication is necessary when convincing someone to receive a vaccine. Holzhausen et al (2022) taught students how to apply the CRAAP test when evaluating information. They found that after this lesson, students were able to identify examples that contained vaccine misinformation.…”
Section: Information Literacy During the Covid-19 Pandemicmentioning
confidence: 99%